Nurse's Attitudes and Acceptance toward COVID-19 Vaccination at Basrah Specialist Hospital for Children in Basrah City - Dawood , Zainab Salman; Jassim, Khadija Mohammed; Abd, Mohammed Talib (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Across sectional study design was used in the present study which conducted at Basrah Specialist Hospital for Children in Basrah City in order to detect nurse's attitudes and acceptance toward COVID-19 vaccination . The period of the study extended from 1 of August to 1st of November, 2021. A non - probability purposive sample of (50) nurses was selected from different wards in Basrah Specialist Hospital for Children . A closed- ended questionnaire composed of three parts which measure nurse's attitudes and acceptance toward COVID-19 vaccination. Results of the study show that (16%) of nurses had low attitudes, (56%) had moderate attitude , and (28%) had high attitude toward COVID-19 vaccination. In addition, the results of study explains that (2%) of nurses had low acceptance, (46%) had moderate acceptance and (52%) had high acceptance toward COVID-19 vaccination. The vast majority of nurses had moderate attitudes and high acceptance toward COVID-19 vaccination .